Blood Levels of Trace Metals and Amyotrophic Lateral Sclerosis - Peters, Tracy L. (Neurotoxicology, 2016)
Some trace metals may increase risk of amyotrophic lateral sclerosis (ALS), whereas others may be beneficial. Our goal was to examine associations of ALS with blood levels of selenium (Se), zinc (Zn), copper (Cu), and manganese (Mn). We conducted a case-control study of 163 neurologist confirmed patients from the National Registry of Veterans with ALS and 229 frequency-matched veteran controls. We measured metal levels in blood using inductively coupled plasma mass spectrometry and estimated odds ratios (ORs) and 95% confidence intervals (CIs) for associations between ALS and a doubling of metal levels using unconditional logistic regression, adjusting for age, gender, and race/ethnicity. ALS was inversely associated with both Se (OR=0.4, 95% CI: 0.2–0.8) and Zn (OR=0.4, 95% CI: 0.2–0.8). Inverse associations with Se were stronger in patients with bulbar compared to spinal onset, worse function, longer diagnostic delay, and longer collection delay; inverse associations with Zn were stronger for those with worse function and longer collection delay. In contrast, ALS was positively associated with Cu (OR=3.4, 95% CI: 1.5–7.9). For Mn, no linear trend was evident (OR=0.9, 95% CI: 0.6–1.3, P(trend)=0.51). Associations of Se, Zn, Cu, and Mn with ALS were independent of one another. Adjustment for lead levels attenuated the positive association of ALS with Cu but did not change associations with Se, Zn, or Mn. In conclusion, Se and Zn were inversely associated with ALS, particularly among those with worse function, suggesting that supplementation with these metals may benefit such patients, while Cu was positively associated with ALS. Deficiencies of Se and Zn and excess Cu may have a role in ALS etiology.